Minimising damage to houses by designing for high internal pressures - Parackal, Korah; Boughton, Geoff; Henderson, David; Falck, Debbie (Frontiers in Built Environment, 2022)
Internal pressurisation of buildings during a severe wind event, such as a tropical cyclone or thunderstorm, can often cause severe structural failures, as observed during damage investigations. Wind loading standards worldwide provide design data for internal pressure design. However, the implementation of these data often depends on the location of the building in relation to the levels of wind hazard in the relevant country. Recent observations during Tropical Cyclone (TC) Seroja in an intermediate wind region (wind region B) in Western Australia indicated the need for the design for full internal pressures of buildings in this wind region. This paper presents an overview of the damage investigation conducted after TC Seroja that highlights significant damage to buildings due to the lack of design for internal pressures. Additionally, a case study of a house modelled using the vulnerability analysis software VAWS is presented showing the improvements in the performance of buildings designed for internal pressures. TheVAWS models showed that both the design for full internal pressure and the use of debris rated shutters were both effective at reducing the level of serious structural damage and making houses more resilient. The robustness and resilience of buildings increase significantly if they are designed for high internal pressure because the failure of a window or door (a local failure) will not lead to a major structural failure.